1993
DOI: 10.1007/bf00212605
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genome analysis of mungbean (Vigna radiata L. Wilczek) and cowpea (V. unguiculata L. Walpers) using RFLP mapping data

Abstract: Genome relationships between mungbean (Vigna tradiata) and cowpea (V. Unguiculata) based on the linkage arrangement of random genomic restriction fragment length polymorphism (RFLP) markers have been investigated. A common set of probes derived from cowpea, common bean (Phaseolus vulgaris), mungbean, and soybean (Glycine max) PstI genomic libraries were used to construct the genetic linkage maps. In both species, a single F2 population from a cross between an improved cultivar and a putative wild progenitor sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
64
3

Year Published

1996
1996
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(68 citation statements)
references
References 59 publications
0
64
3
Order By: Relevance
“…Marker orders and LGs were similar in both taxa with syntenic association appeared on 10 genomic regions although duplication and rearrangement exist (Menancio et al, 1993). Mungbean and azuki bean linkage maps share several conserved genome segments without or with some rearrangement (Kaga et al, 2000;Isemura et al, 2007) and showed that LG 1, 2, 3, 4, 8 and 11 of mungbean map (Menancio et al, 1993) correspond respectively to LG (1,4,10, 8, 2 and 9) of azuki bean map (Han et al, 2005). Genome conservation between mungbean and common bean appears to be higher than between mungbean and cowpea (Boutin et al, 1995) or azuki bean (Kaga et al, 2000).…”
Section: Comparative Genome Mappingmentioning
confidence: 90%
See 1 more Smart Citation
“…Marker orders and LGs were similar in both taxa with syntenic association appeared on 10 genomic regions although duplication and rearrangement exist (Menancio et al, 1993). Mungbean and azuki bean linkage maps share several conserved genome segments without or with some rearrangement (Kaga et al, 2000;Isemura et al, 2007) and showed that LG 1, 2, 3, 4, 8 and 11 of mungbean map (Menancio et al, 1993) correspond respectively to LG (1,4,10, 8, 2 and 9) of azuki bean map (Han et al, 2005). Genome conservation between mungbean and common bean appears to be higher than between mungbean and cowpea (Boutin et al, 1995) or azuki bean (Kaga et al, 2000).…”
Section: Comparative Genome Mappingmentioning
confidence: 90%
“…trait loci, map-based cloning, and physical map construction. Now, F 2 or recombinant inbred lines (RILs populations) based six molecular linkage maps for mungbean have been published (Menancio et al, 1993;Boutin et al, 1995;Lambrides et al, 2000;Humphry et al, 2002). A Linkage map form mungbean population developed from inter subspecific crosses of VC 3980, cultivated x TC1966, wild from Madagascar and Berken, cultivated x ACC41, wild from Australia have been published using RFLP and RAPD markers.…”
Section: Molecular Marker Technologies and Their Utilitymentioning
confidence: 99%
“…Genetic maps of cowpea have been established by Fatokun et al (1992Fatokun et al ( , 1993, Menancio-Hautea et al (1993), MenĂ©ndez et al (1997), Ubi et al (2000) and OuĂ©draogo et al (2002). Of these, the latter, building on the earlier version developed by MenĂ©ndez et al (1997), is the most current and complete map and will be discussed in this article (http://pubs.nrc-cnrc.gc.ca/ cgi-bin/rp/rp2_abst_f?gen_g01-102_45_ns_nf_gen1-02).…”
Section: Integrated Cowpea Linkage Mapmentioning
confidence: 99%
“…The bestdocumented cases of genome conservation are from the grass family (Poaceae), where rice (Oryza sativa) with its small genome has been selected as a nodal species to study the economically important cereal crops including corn (Zea mays), sorghum (Sorghum bicolor), wheat (Triticum aestivum), and barley (Hordeum vulgare; Devos and Gale, 2000). Extensive macrosynteny has also been observed within the Solanaceae (Tanksley et al, 1992), the Brassicaceae (Kowalski et al, 1994;Lagercrantz and Lydiate, 1996;Lagercrantz, 1998;O'Neill and Bancroft, 2000;Acarkan et al, 2000), and the Fabaceae (Weeden et al, 1992;Menacio-Hautea et al, 1993;Torres et al, 1993;H.-K. Choi and D.R. Cook, unpublished data).…”
mentioning
confidence: 99%